Effective isolation and expansion of human limbal niche cells - Gießl, Andreas; Polisetti, Naresh; Li, Shen; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Identification, Isolation, and Characterization of Melanocyte Precursor Cells in the Human Limbal Stroma - Li, Shen; Zenkel, Matthias; Kruse, Friedrich; Gießl, Andreas; Schlötzer-Schrehardt, Ursula (International Journal of Molecular Sciences, 2022)
Given their vital role in the homeostasis of the limbal stem cell niche, limbal melanocytes have emerged as promising candidates for tissue engineering applications. This study aimed to isolate and characterize a population of melanocyte precursors in the limbal stroma, compared with melanocytes originating from the limbal epithelium, using magnetic-activated cell sorting (MACS) with positive (CD117/c-Kit microbeads) or negative (CD326/EpCAM or anti-fibroblast microbeads) selection approaches. Both approaches enabled fast and easy isolation and cultivation of pure limbal epithelial and stromal melanocyte populations, which differed in phenotype and gene expression, but exhibited similar functional properties regarding proliferative potential, pigmentation, and support of clonal growth of limbal epithelial stem/progenitor cells (LEPCs). In both melanocyte populations, limbus-specific matrix (laminin 511-E8) and soluble factors (LEPC-derived conditioned medium) stimulated melanocyte adhesion, dendrite formation, melanogenesis, and expression of genes involved in UV protection and immune regulation. The findings provided not only a novel protocol for the enrichment of pure melanocyte populations from limbal tissue applying easy-to-use MACS technology, but also identified a population of stromal melanocyte precursors, which may serve as a reservoir for the replacement of damaged epithelial melanocytes and an alternative resource for tissue engineering applications.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cultivation; laminin 511-E8; limbal stem cell niche; limbal stem cells; limbal stroma; magnetic-activated cell sorting; melanocytes

Laminin-511-E8 promotes efficient in vitro expansion of human limbal melanocytes - Polisetti, Naresh; Gießl, Andreas; Li, Shen; Sorokin, Lydia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Scientific Reports, 2020)
Limbal melanocytes, located in the basal epithelial layer of the corneoscleral limbus, represent essential components of the corneal epithelial stem cell niche, but, due to difficulties in their isolation and cultivation, their biological roles and potential for stem cell-based tissue engineering approaches have not been comprehensively studied. Here, we established a protocol for the efficient isolation and cultivation of pure populations of human limbal melanocytes, which could be expanded at high yield by using recombinant laminin (LN)-511-E8 as culture substrate. Co-cultivation of limbal melanocytes with limbal epithelial stem/progenitor cells on fibrin hydrogels pre-incubated with LN-511-E8 resulted in multilayered stratified epithelial constructs within ten days. By reproducing physiological cell–cell and cell–matrix interactions of the native niche environment, these biomimetic co-culture systems provide a promising experimental model for investigating the functional roles of melanocytes in the limbal stem cell niche and their suitability for developing advanced epithelial grafts for ocular surface surface reconstruction.
CRIS-Team Scopus Importer:2020-07-17